2006
DOI: 10.1073/pnas.0602317103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for PKR activation by PACT or dsRNA

Abstract: antiviral mechanism ͉ autoinhibition ͉ NMR ͉ peptide activator ͉ protein kinase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 50 publications
0
114
0
2
Order By: Relevance
“…Two models currently describe PKR activation: the autoinhibition and dimerization models (50). It was suggested that binding of either dsRNA or PACT to PKR may interrupt intramolecular interaction between the kinase and dsRNA-binding domains, leading to an open conformation of the PKR molecule and allowing autophosphorylation to occur (49). NF90 is phosphorylated by PKR in its RBD (6).…”
Section: /2mentioning
confidence: 99%
See 1 more Smart Citation
“…Two models currently describe PKR activation: the autoinhibition and dimerization models (50). It was suggested that binding of either dsRNA or PACT to PKR may interrupt intramolecular interaction between the kinase and dsRNA-binding domains, leading to an open conformation of the PKR molecule and allowing autophosphorylation to occur (49). NF90 is phosphorylated by PKR in its RBD (6).…”
Section: /2mentioning
confidence: 99%
“…Phosphorylation of PKR is essential for activation of its function, and it can be regulated by host RNA-binding proteins other than dsRNA (47)(48)(49). Two models currently describe PKR activation: the autoinhibition and dimerization models (50).…”
Section: /2mentioning
confidence: 99%
“…48 Convincing NMR titration, immunoprecipitation and mutagenesis data was presented to show that this region in the N-lobe of the kinase is responsible for the autoinhibitory kinase-RBD2 interaction. In contrast, we observe only minor changes in the implicated region and attribute these to RBD1 binding.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…On the other hand, domain 3, which, in vitro, can activate PKR by itself, binds, with low affinity, to a specific region in the kinase domain of PKR (20). We have recently identified the PACT binding motif (PBM) in this region of PKR (21). Moreover, we demonstrated intramolecular interaction between PBM and dsRBM2 of PKR.…”
mentioning
confidence: 99%